Ostracism and Violence in The Contemporary History of Religions - Saleem, Muhammad Mubashir (South Asian Journal of Religion and Philosophy (SAJRP), 2024)
Psychology explores the motivation for certain kinds of behaviour such as violence. This study investigates the correlation between religion-based violence and ostracism. There is evidence to suggest that those who are chronically ostracized could become involved in forms of extremism and violence that is not necessarily inspired by their religious tradition. Religious minorities belonging to any faith sometimes join extremist groups after being ostracized in order to compensate for their basic human need to belong. If Islamophobia is understood as the exclusion of Muslims from western societies, it is one form of ostracism. Some Muslims in Europe feel that the wider society does not recognize them as full citizens. Moreover, anti-Semitism and negative attitudes to the Christian community in Pakistan are also examples of ostracism. Policy-makers could take steps to reduce the danger of the violence provoked by ostracism.